Український модерн в архітектурі - Лисенко, А. А. (ХНУРЕ, 2020)
This work is dedicated to the Ukrainian modern style, which spread throughout the territory of Ukraine in the first half of the 20th century. In it, unlike previous ones, there is a huge variety of forms in all elements of structures. The largest number of masterpieces has been preserved in Lviv, Kharkiv, Kyev and Odesa, erected by such famous creators of that era as Vasil Krichevsky, Viktor Trotsenko, Kostyantin Zhukov. The author concludes that this period is significant in the history of Ukraine.
Keywords: культурне розмаїття; українознавство; традиції; культура